Development of a Mitochondrially Targeted Probe Based on Polyethyleneimine‐(3‐carboxypropyl) Triphenylphosphine‐Modified Quantum Dots for Fluorescence Imaging. Issue 2 (28th December 2020) - Zhang, Zhi-Qiang; Ren, Bin; Qiao, Lu-Lu; Zhang, Yan-Bin; Liu, Yong-Fang; Xu, Jing-Jing; Yang, Xiaojing; Zhao, Mei-Xia
Abstract : Quantum dots (QDs) are semiconductor particles of a few nanometers in size that have unique optical and electronic properties. These properties include stable high‐intensity fluorescence and strong resistance to light bleaching, making them attractive as imaging agents. Mitochondria play many extremely important roles in cells. During apoptosis, several characteristics of mitochondria change that are exploited using fluorescent imaging probing including QDs. Herein, a mitochondria‐targetable fluorescence probe (CdSe/ZnS@PEI‐TPP) based on QDs is developed by covalently binding low‐molecular‐weight polyethyleneimine (PEI)‐modified CdSe/ZnS QDs with the small molecule (3‐carboxypropyl) triphenylphosphine (TPP). CdSe/ZnS@PEI‐TPP QDs have excellent optical emission properties. The ultraviolet and visible spectrophotometry (UV–vis) and fluorescence spectra of QDs show that TPP is successfully integrated into the QD structure. Cell proliferation measurements from 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assays demonstrate that the modified QDs are less cytotoxic. The modified QDs show high fluorescence in cancer cells in vitro. These data demonstrate that CdSe/ZnS@PEI‐TPP QDs successfully target mitochondria and are used as fluorescence imaging probes. Abstract : CdSe/ZnS@PEI‐TPP quantum dots (QDs) have excellent optical emission properties and are less cytotoxic. The modified QDs have high fluorescence in cancer cells in vitro and successfully target mitochondria. The modified QDs are used as fluorescence imaging probes.